2002
DOI: 10.1172/jci0212337
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial induction of autoantibodies to β2-glycoprotein-I accounts for the infectious etiology of antiphospholipid syndrome

Abstract: The antiphospholipid syndrome (APS) is characterized by the presence of pathogenic autoantibodies against β2-glycoprotein-I (β2GPI). The factors causing production of anti-β2GPI remain unidentified, but an association with infectious agents has been reported. Recently, we identified a hexapeptide (TLRVYK) that is recognized specifically by a pathogenic anti-β2GPI mAb. In the present study we evaluated the APS-related pathogenic potential of microbial pathogens carrying sequences related to this hexapeptide. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(46 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…Autoantibody production against phospholipid binding proteins has been documented as a consequence of exposure to infectious agents 24, 25 but conflicting reports still exist about the appearance of these aPL after vaccine administration. In healthy subjects given the Hepatitis B recombinant vaccine who exhibited changes in aPL values, a significant increase was observed in β2GPI values but not in aCL values 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibody production against phospholipid binding proteins has been documented as a consequence of exposure to infectious agents 24, 25 but conflicting reports still exist about the appearance of these aPL after vaccine administration. In healthy subjects given the Hepatitis B recombinant vaccine who exhibited changes in aPL values, a significant increase was observed in β2GPI values but not in aCL values 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Transient anti-β 2 GPI antibody production was induced experimentally in vivo by injection of pathogen proteins or peptides [26, 76]. Molecular mimicry has been best studied using antibodies that target the TLRVYK sequence in domain III [26, 25].…”
Section: Molecular Mimicry Aps and β2gpimentioning
confidence: 99%
“…Transient anti-β 2 GPI antibody production was induced experimentally in vivo by injection of pathogen proteins or peptides [26, 76]. Molecular mimicry has been best studied using antibodies that target the TLRVYK sequence in domain III [26, 25]. Notably, the Shoenfeld group showed that mice immunized with proteins from Haemophilus influenzae , Neisseria gonorrhoeae , or tetanus toxoid, which all share sequence homology to the core region TLRVYK.…”
Section: Molecular Mimicry Aps and β2gpimentioning
confidence: 99%
“…There are also other acquired causes as the presence of heparin in the sample, being from treatment or contamination and the lupus anticoagulant (LA). This last one is caused by the presence of antiphospholipid antibodies, IgG and/or IgA immunoglobulins, which are present in almost 23% of apparently healthy children [2]- [4], most of all in the younger population [5] in which they are usually transitory in association with infections [4] [6] [7]. Duration in circulation of the lupus anticoagulant is not yet exactly known, but to be considered transitory, not related with autoimmune diseases as the antiphospholipid syndrome, it must be less than 12 weeks [6] [8]- [10].…”
Section: Introductionmentioning
confidence: 99%